Estratégias metacognitivas no ensino e aprendizagem de ciências para alunos com transtorno do espectro autista - Batista, Rochelle da Silva (Universidade Federal do Pará, 2024)
Teaching biological science for students with Autistic Spectrum Disorder (ASD), as well as for other students, should consider activities that encourage the construction of critical thinking and intellectual autonomy, which are important for the full exercise of citizenship in contemporary society. In this context, this study aimed to build an Educational Product (Metacognitive strategies for teaching science to students with ASD: reading and interpreting popular science texts) that made it possible to analyse the limits and possibilities of using certain metacognitive strategies as well as possible contributions to biological science teaching and learning process of students with ASD, having as based on the metacognitive theory proposed by John Flavell. With a qualitative approach, of the participant observation type, activities including reading and comprehensive of texts about the topic of the pandemic were developed. The approach was applied with three students diagnosed with autism spectrum disorder, aged between fourteen and seventeen years of an Educational Assistance Center Specialized, located within a philanthropic institution in Belém/Pará/Brazil. Video recordings of the classes and written records prepared by the students were collected for further analysis. Content Analysis was used, using the metacognitive skills coding structure proposed in recent research on the subject. The results suggest that it is feasible and promising to use metacognitive teaching-learning strategies with students with ASD. It contributed to the establishment of an environment that trigger the dialog and motivate students to acquire and make use of metacognitive skills. In addition to the results presented, this research discusses interesting possibilities for other studies regarding the application of suggestions from the research field of metacognition to educational activities for students with ASD, which are still little explored in our country.